SUNNAH PERSPECTIVE CHARACTER EDUCATION METHODS IN SHAHIH BUKHARI - Hamdani; Abdul Rahman (RADJA PUBLIKA, 2023)
This research has a background that in the era of society 5.0, education in Indonesia has not been fully successful in forming a superior and characterized young generation who are declining day by day. Education requires a reference source or model that is used as an example for educational academics in improving and forming a noble national character. The Prophet Muhammad saw through his sunnah contained in the Book of Sahih Bukhari which is the main reference in one's character education method. The purpose of this study is to explore character education methods in the perspective of the sunnah contained in the Book of Sahih Bukhari. This type of research is a qualitative literature research. Library research collects data and information with the help of various materials in the literature. The data collection techniques in this study used documentation. While the data analysis technique used is content analysis (content analysis). The results of this study are character education methods in the sunnah perspective, namely, 1) exemplary method, 2) dialogue method, 3) story method, 4) habituation method, 5) parable method, 6) targhib and tarhib methods. This research contributes as a reinforcing and alternative idea for educators in choosing and using character building methods for students. 5) The parable method, 6) The targhib and tarhib methods. This research contributes as a reinforcing and alternative idea for educators in choosing and using character building methods for students. 5) The parable method, 6) The targhib and tarhib methods. This research contributes as a reinforcing and alternative idea for educators in choosing and using character building methods for students.